Identification and characterization of a novel HLA‐B hybrid allele, B*08:132 with Next Generation Sequencing. Issue 5 (7th October 2014) - Papazoglou, A.; Gasiewski, A.; Huynh, A.; Duke, J.; Ferriola, D.; Rogers, M.; Lind, C.; Monos, D. S.
<x xml:space="preserve">Abstract</x> The new allele is a hybrid between B*08:01:01 and B*42:01:01.